Hubungan Pengetahuan Bumil TM III tentang Tanda Bahaya Kehamilan dengan Pemanfaatan Buku KIA - Fina Alfiana; Yuniasih Purwaningrum; Ida Prijatni (ARTERI : Jurnal Ilmu Kesehatan, 2021)
At this time, many pregnant women don’t understand the importance of KIA Books. KIA books are often assumed to be a control card that must carry. But too much of information contained has an impact KIA books being less applied by pregnant woman. The purpose of this study was to determine the relationship between knowledge of pregnant women TM III with danger signs of pregnancy use of KIA books. This research design uses probability sampling by means of cluster sampling. The data were taken from a questionnaire given by pregnant women TM III. Research subject is pregnant women with TM III, data were analyzed by the spearman rank test. This study involved 62 pregnant women TM III. The result is 19 respondents (30.6%) have good knowledge, in detail 15 respondents (24.4%) use KIA books and 4 respondents (6.5%) didn’t use KIA books. Meanwhile, 21 respondents (33.9%) were knowledgeable enough, in detail 11 respondents (17.7%) used KIA books and 10 respondents (16.1%) didn’t use KIA books. Then, 22 respondents (35.5%) had less knowledge, indicating that 16 respondents (25.8%) used KIA books and 6 respondents (25.8%) didnt use KIA books. Spearman rank test results obtained value 0.764 > = 0.05. In conclusion, there is no relationship between the knowledge of pregnant women TM III about the danger signs of pregnancy with the use of the KIA books. So it is important to understand the KIA books for pregnant women with TM III to detect the danger signs of pregnancy so that they can be handled quickly and appropriately.